Kesesuaian Wisata pada Ekowisata Sungai Mudal Kabupaten Kulonprogo DIY - Prasetya, Johan Danu; Ayumadany, Maulidya Anggun; Gomareuzzaman, Muammar (Jurnal Lingkungan Kebumian Indonesia, 2023)
Tourism is one of the factors that have a role in the Indonesian economy. Even so, in its sustainability, it must pay attention to the existence of ecological sustainability. Good tourism activity is sustainable tourism. One of how environmentally friendly development can be done is to prevent pollution and damage to nature. This study aims to determine the suitability of existing tourism in Sungai Mudal Ecotourism. Importance knowing the suitability of tourism can contribute to anticipating the occurrence of degradation or damage to nature. The method used in this research is survey and field mapping to obtain tourism suitability parameter data. The results obtained in this study consist of 3 types of tourism suitability which include the use of playing water with a Tourism Suitability Index (IKW) = 2.55 (Very Appropriate, IKW 2.50), the use of sitting relaxed has a tourism suitability index of 1.5 (Not suitable, 1 IKW 2.0 ), and the use of camping has a tourism suitability index of 1.975 ( Not suitable, 1 IKW 2.0).